2021
DOI: 10.3389/fmicb.2020.618144
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids as Alternatives for Antibiotic Growth Promoters Alter the Intestinal Structure and Microbiota and Improve the Growth Performance in Broilers

Abstract: The present study aimed to investigate the effects of organic acids (OA) as alternatives for antibiotic growth promoters (AGP) on growth performance, intestinal structure, as well as intestinal microbial composition and short-chain fatty acids (SCFAs) profiles in broilers. A total of 336 newly hatched male Arbor Acres broiler chicks were randomly allocated into 3 dietary treatments including the basal diet [negative control (NC)], the basal diet supplemented with 5 mg/kg flavomycin, and the basal diet suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 70 publications
(57 reference statements)
7
54
0
Order By: Relevance
“…The previous study has demonstrated that dietary supplemented with mixed organic acid could improve performance ( 14 ), immune function ( 5 , 15 ), intestinal morphology as well as intestinal microbiota ( 10 , 16 ). Also, numerous scholars have illustrated the mechanism of MOA and summarized the benefits of MOA in livestock and poultry ( 4 , 17 ), especially in weaning pigs ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study has demonstrated that dietary supplemented with mixed organic acid could improve performance ( 14 ), immune function ( 5 , 15 ), intestinal morphology as well as intestinal microbiota ( 10 , 16 ). Also, numerous scholars have illustrated the mechanism of MOA and summarized the benefits of MOA in livestock and poultry ( 4 , 17 ), especially in weaning pigs ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher abundance of genus Frisingicoccus, Eubacterium_hallii_group, and Ruminococcus was observed in xylanase un-supplemented broilers on day 21, and higher abundance of Peptococcaceae and Bacillaceae was shown in broilers from CON group on day 42. These bacteria belong to phylum Firmicutes; however, this phylum is thought to contribute to the production of SCFA (Dai et al, 2021). Supplementing xylanase could also decrease the abundance of family Propionibacteriaceae on day 21, and bacteria belonging to family Propionibacteriaceae could also promote the production of SCFA.…”
Section: Correlations Between Ileal Microbiota Lactate and Acetate Levels Morphology And Immune Factorsmentioning
confidence: 99%
“…However, their continued use in animal nutrition developed antibiotic resistance and drug residues, which resulted in global public health issues and exacerbating poverty in the 21st century [ 9 , 10 , 11 ]. In this regard, organic acids are selected as a promising feed additive in poultry production due to their ability to maintain gut barrier cellular integrity, modulate intestinal microbiota, improve digestion and nutrient absorption rate and contribute to improved production performance [ 6 , 12 , 13 ]. BA as a short chain fatty acid (SCFA) and CA as a tricarboxylic acid (TCA) gained considerable attention as representative organic acids in poultry production.…”
Section: Introductionmentioning
confidence: 99%